Polyvinyl Alcohol–Borax Slime as Promising Polyelectrolyte for High‐Performance, Easy‐to‐Make Electrochromic Devices. Issue 2 (2nd February 2015) - Alesanco, Yolanda; Palenzuela, Jesús; Viñuales, Ana; Cabañero, Germán; Grande, Hans J.; Odriozola, Ibon
Abstract The front cover artwork is provided by the Materials Division at IK4‐CIDETEC (Spain). The image tries to associate the electrochromic device (ECD) based on PVA–borax slime with characters from HE‐MAN and MASTERS OF THE UNIVERSE. Thus, Violoman (viologen) is attacked by the villain Skelectrode (electrodes) by pouring a slime (PVA–borax polyelectrolyte slime) and electric discharges on him. Find out more by reading the full Article at 10.1002/celc.201402265.